Therapy-related lipid profile changes among patients' on highly active antiretroviral treatment in Kano, North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Highly active antiretroviral therapy (HAART), an effective treatment for human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) results in significant reduction in viral load, increased CD4 cell count and improved quality of life of people living with HIV/AIDS. HAART being a life-long treatment increases the propensity for manifesting long-term complications like changes in lipid profile.Aims:This study set out to assess therapy induced lipid profile changes among patients on HAART in Kano North-Western Nigeria.Design:Cross-sectional.Settings:This study was conducted at the HIV clinic of the Aminu Kano Teaching Hospital, Nigeria.Subjects and Methods:The study group consist of 120 patients on HAART (Group I) and 120 HAART naïve patients (Group II).Results:The mean values of cholesterol, triglyceride (TG), low-density lipoprotein cholesterol (LDLC) and high-density lipoprotein cholesterol (HDLC) were 4.15 mmol/L ± 1.03, 1.79 mmol/L ± 0.67, 2.79 mmol/L ± 0.98 and 0.99 mmol/L ± 0.28 in Group I, respectively and were statistically significantly higher than 3.50 mmol/L ± 0.94, 1.21 mmol/L ± 0.55, 1.13 mmol/L ± 0.45 and 0.91 mmol/L ± 0.30 in Group II (P< 0.05). The prevalence of dyslipidaemia was high total cholesterol in Group I (25%) Group II (7.5%): high TG in Group I (30%) > Group II (7.5%): High LDLC in Group I (30%) > Group II (17.5%) low HDLC in Group II (40%) >xb Group I (35%). The prevalence of hypertriglyceridemia was 43% in the protease inhibitor (PI) based and 16.7% in 'the non-PI based groups respectively.Conclusions:This study confirms the existence of artherogenic lipid profile in patients on HAART (especially those on PI-based regimen) and further underscores the importance of close monitoring to prevent cardiovascular complications.